Cosmetotextiles with Gallic Acid: Skin Reservoir Effect. (11th April 2013) - Martí, Meritxell; Alonso, Cristina; Martínez, Vanessa; Lis, Manel; de la Maza, Alfons; Parra, José L.; Coderch, Luisa
Abstract : The antioxidant gallic acid (GA) has been incorporated into cotton (CO) and polyamide (PA) through two different vehicles, that is, liposomes and mixed micelles, and their respective absorption/desorption processes have been studied. Moreover, in vitro percutaneous absorption tests of different cosmetotextiles have been performed to demonstrate antioxidant penetration within the layers of the skin. When GA was embedded into the cosmetotextiles, it always promoted a reservoir effect that was much more marked than that observed for polyamide. Similar penetration was observed in the textiles treated with GA in mixed micelles or liposomes in such compartments of the skin as the stratum corneum, epidermis, and even the dermis. GA was detected in receptor fluid only when CO was treated with MM. This methodology may be useful in verifying how encapsulated substances incorporated into textile materials penetrate human skin. Indeed, such materials can be considered strategic delivery systems that release a given active compound into the skin at specific doses.